2017
DOI: 10.1177/0269881117714047
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction risk and antipsychotics use revisited: a meta-analysis of 10 observational studies

Abstract: Objective: Associations between antipsychotic agent (AP) use and myocardial infarction (MI) risk have been inconsistent and remain controversial. We therefore conducted a meta-analysis of observational studies to address this knowledge gap.Method: Detailed electronic database searches were performed to identify reports of observational studies that evaluated the association between AP use and the risk of MI.Pooled odds ratios were calculated using random or fixed-effects models. Results:In total, 4 case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
4
12
0
Order By: Relevance
“…To the best of our knowledge, this is the largest study on the sex difference of the association between antipsychotics and IHD incidence in a primary care population. Our results are consistent with a previous study of 277,817 adults which showed a more substantial elevation of the risk of IHD among women with various psychiatric disorders treated with antipsychotics compared with men [ 16 ], but are inconsistent with a meta-analysis which showed that the association was slightly stronger among men than among women in a pooled analysis [ 5 ]. This inconsistent finding may have been due to the different patient populations adopted by the included studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To the best of our knowledge, this is the largest study on the sex difference of the association between antipsychotics and IHD incidence in a primary care population. Our results are consistent with a previous study of 277,817 adults which showed a more substantial elevation of the risk of IHD among women with various psychiatric disorders treated with antipsychotics compared with men [ 16 ], but are inconsistent with a meta-analysis which showed that the association was slightly stronger among men than among women in a pooled analysis [ 5 ]. This inconsistent finding may have been due to the different patient populations adopted by the included studies.…”
Section: Discussionsupporting
confidence: 82%
“…This inconsistent finding may have been due to the different patient populations adopted by the included studies. In fact, most reviewed studies only included patients with certain psychiatric disorders, such as schizophrenia, unlike our current study which observed a much more diverse population of primary care patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mediation model (i.e., CMmental healthphysical health) has convincing support from previous longitudinal studies and could be most plausible for physical health outcomes that are "stress-related" such as COPD. Indeed, previous evidence suggests that poor mental health is associated (directly or indirectly via medication) with an increased risk of a wide range of physical health outcomes (Blanchette et al, 2008;Cohen et al, 2000;Correll et al, 2015;Correll et al, 2017;Coupland et al, 2011;Hippisley-Cox et al, 2001;Huang et al, 2017;Mock and Arai, 2011;Pan et al, 2010;Rubin et al, 2008;Scott et al, 2011;Tata et al, 2005;Vancampfort et al, 2015;Yoon et al, 2013). For instance, use of tricyclic tranquilizers can cause metabolic syndrome (Van Reedt Dortland et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although both trazodone and atypical antipsychotics have been associated with an increased risk of falls and fractures, anti psychotic use has also been associated with an increased risk of myocardial infarction and stroke in patients with dementia. 12,50,80…”
Section: Discussionmentioning
confidence: 99%